Phenology, thermal demand, and maturation development of the ‘BRS Vitória’ grape cultivated on different rootstocks in subtropical conditions - Callili, Daniel [UNESP]; Sánchez, Camilo André Pereira Contreras [UNESP]; Campos, Olivia Pak [UNESP]; Carneiro, Débora Cavalcante Dos Santos [UNESP]; Scudeletti, Ana Carolina Barduzzi [UNESP]; Tecchio, Marco Antonio [UNESP] (FapUNIFESP (SciELO), 2023)
The purpose of this study was to assess how ‘IAC 572’, ‘IAC 766’, and ‘Paulsen 1103’ rootstocks affected the duration of phenological phases, thermal de-mand, and chemical evolution throughout production cycle of the ‘BRS Vitória’ table grape cultivated in subtropical conditions. The duration of the following pheno-logical stages was measured in days after pruning throughout two production sea-sons: budburst, flowering, setting, veraison, and harvest date. The thermal demand was determined using the degree-day concept. Titratable acidity, pH, soluble solids, and the maturation index were all measured throughout berry maturation. In gen-eral, the rootstocks ‘IAC 572’ and ‘IAC 766’ increased vine precocity in comparison to ‘Paulsen 1103’ during the early phenological phases. However, the vines grafted on ‘Paulsen 1103’ were earlier in the later phases, that is, at the veraison and at the harvest date, when compared to those grafted on the rootstocks ‘IAC 572’ and ‘IAC 766’. Under subtropical conditions, the total cycle period of the ‘BRS Vitória’ vine varied from 131 to 143 days, with thermal demands ranging from 1,545 to 1,725 DD. In comparison to the ‘IAC 572’ and the ‘IAC 766’, the ‘Paulsen 1103’ supplied the berries with a higher accumulation of soluble solids and a higher maturation index.
Fenologia, demanda térmica e evolução da maturação da uva ‘BRS Vitória’ cultivada sobre diferentes porta-enxertos em condições subtropicais
Keywords: chemical analysis; grafting; seedless grape; subtropical viticulture; table grapes